APLIKASI PENGGUNAAN ANALISIS MODEL MAXIMS PADA PROSES GRAZING RATE COPEPODA TERHADAP PEMBERIAN DUNALIELLA SALINA DAN CHLORELLA SP - Rose Dewi; Muhammad Zainuri; Hadi Endrawati (Jurnal Harpodon Borneo, 2011)
The aim of this research was to determine the copepod daily feeding to Dunaliella salina and Chlorella sp because the research of copepod daily consumption to the phytoplankton in the sea was a part of discovering the water productivity. The determination was needed in the laboratory experimental method, in order to qualifying the biomass and energy transfer of sea food web / chain. The observation based on the laboratory experimental method and conducted in the Hatcehery and Laboratory of Alga, Marine Station, Teluk Awur Jepara. Four treatment were applied during the observation, i.e.: A. D.salina 20 litre; B. D.salina  2 litre; C. Chlorella sp 20 litre; D. Chlorella sp 2 liter. The copepod grazing rate was determined base on parameter of cell phytoplankton/ ml/ hour/ copepode. There were 4 series observation. The observations were done for 36 hours with 3 hours interval. The data collected was arranged as copepod daily consumption and analyzed using MAXIMS Analysis Models. The highest copepod daily grazing rate was 88.02 ± 44.18 cell phytoplankton/ ml/ hour/ copepod for D.salina on 20 liter volume of media. While the lowest one 50.16 ± 43.99 cell phytoplankton/ ml/ hour / copepod for Chlorella sp on 2 liters volume media. The Copepod daily grazing model tends to form a constant model for D.salina on 20 liters of media and proportional model for 2 liters volume of media. The Chlorella sp on 2 liters volume of media graze by the copepod showed the same model for constant and proportional model. The water quality of the media remained in tolerance range to support the grazing rate of copepod to the phytoplankton during the research.